A Tapered Cuff Tracheal Tube Decreases the Need for Cuff Pressure Adjustment After Surgical Retraction During Anterior Cervical Spine Surgery: A Randomized Controlled, Double-Blind Trial - Li, Yi-Shiuan; Tan, Elise Chia-Hui; Tsai, Yueh-Ju; Mandell, Mercedes Susan; Huang, Shiang-Suo; Chiang, Ting-Yun; Huang, Wen-Cheng; Chang, Wen-Kuei; Chu, Ya-Chun (Frontiers in Medicine, 2022)
Background Surgical retraction to expose the vertebrae during anterior cervical spine surgery increases tracheal tube cuff pressure and may worsen postoperative sore throat and dysphonia. This randomised double-blind study investigated the effect of cuff shape on intraoperative cuff pressure and postoperative sore throat and dysphonia. Methods Eighty patients were randomised to tracheal intubation with a tapered cuff or a conventional cylindrical high-volume low-pressure cuff (control) during anaesthesia. Intraoperative cuff pressures were compared. The primary outcome was the incidence of pressure adjustment needed when the cuff pressure increased to >25 mm Hg after surgical retraction. The secondary outcome was the incidence of postoperative sore throat and dysphonia. Results The incidence of pressure adjustment after surgical retraction was significantly lower in the tapered group than in the control group (13% vs. 48%; P=0.001; relative risk reduction, 74%). The median [interquartile range (IQR)] cuff pressure (mm Hg) was significantly lower for the tapered cuff than for the control cuff before surgical retraction [9 (7–12) vs. 12 (10–15); P<0.001] and after retraction [18 (15–23) vs. 25 (18–31); P=0.007]. The median (IQR) postoperative dysphonia score assessed by a single speech-language pathologist was lower in the tapered group than in the control group [4 (3–6) vs. 5.5 (5–7); P=0.008]. Conclusions A tapered cuff tracheal tube decreased the need for the adjustment of cuff pressure after surgical retraction during anterior cervical spine surgery, thereby avoiding intraoperative pressure increase. It also has a better outcome in terms of dysphonia. Clinical trial registration: www.clinicaltrials.gov (NCT04591769); registered 19 October 2020